46. EVALUATING ACUTE TOXICITY AND LIVER PROTECTIVE EFFECT ON PARACETAMOL-INDUCED HEPATOTOXICITY IN MICE MODEL OF BAO DUONG CAN PC TABLET (Vietnam Journal of Community Medicine, 2024)
Objective: Research on acute toxicity and evaluate the liver protective effect of Bao duong can PC tablets on Swiss mice on the model of acute liver injury with Paracetamol.Research objects and methods: Acute toxicity of the research product was conducted on mice orally and determined according to the Litchfied-Wilcoxon method. Evaluation of the liver protective effect of Bao duong can PC tablets on the model of acute liver injury with Paracetamol in Swiss mice.Results: Monitoring showed that mice taking Bao duong can PC at different dosage levels did not show any unusual symptoms within 72 hours after taking the research product. Results of research: the liver protective effect of Bao duong can PC tablets at two dosage levels of 1.44 tablets/kg/day and 4.32 tablets/kg/day on an experimental model of acute hepatitis with Paracetamol shows that a trend of improvement in research indicators.Conclusion: LD50 in Swiss mice of Bao duong can PC has not been determined orally. Bao duong can PC has a liver protective effect on the model of experimental liver damage with Paracetamol.
Keywords: Acute toxicity; Bao duong can PC; the liver protective; Paracetamol; acute liver injury,; Swiss mice